The Effect of Metal Impregnation Of Fe Cu And Co on Surface Area of ZSM-5 Catalyst Analyzed Using Surface Area Analyzer (AAS) - Sihotang, Andreas; Is Heriyanti, Septina; Djangkung Sumbogo Murti, Sri; Mirda Yanti, Fusia; Farizt Ichsan, Ahmad; Adiningtyas Putri, Alya; Riski Gusti, Diah (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2022)
The number of watercrafts in the sea will have an impact on the amount of waste lubricant oil that is discharged into the sea, which ultimately results in pollution. The increasing level of hazardous and toxic materials (B3 waste) is concerned to have a wider impact on public health and environment quality. One of the B3 wastes that requires special handling due to its high quantities is used lubricating oil. Utilization and processing of waste lubricant oil discharged from the ship is an alternative that can be applied to reach efficient consumption of petroleum which is shrinking from year to year. Therefore, we need a processing method that can reduce the pollutants generated from the waste, one of which is the Acid Clay Treatment method. This treatment aims to determine the best conditions for reducing heave metal lead (Pb) through Acid Clay Treatment method and to assess the decrease in Pb concentration contained in used lubricating oil from ship. The adsorbent used was clay that has been activated with sulphuric acid. The processing of used lubricating oil was carried out using three variations, including adsorbent concentration, contact time, and acidity (pH). The test results of used oil lubricating oil processing were 15 gram of adsorbent concentration, 90 minutes of contact time, and pH 4. The Pb reduction efficiency obtained from Acid Clay Treatment method in the best conditions was 53.72%.